Ross Errilly Franciscan Friary, south chancel wall, piscina, base - O'Donovan, Danielle (My University, 2008)
Base of octagonal piscina shaft. From top down moulding comprises: chamfered fillet as necking, bell, roll, bell, plinth.
Piscina
Keywords: chamfered fillet; Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Architecture, Franciscan; Late Medieval; roll moldings; plinth